Heterogeneity of the rice microbial community of the Chinese centuries‐old Honghe Hani rice terraces system. (7th July 2020) - Alonso, Pascal; Blondin, Laurence; Gladieux, Pierre; Mahé, Frédéric; Sanguin, Hervé; Ferdinand, Romain; Filloux, Denis; Desmarais, Eric; Cerqueira, Frédérique; Jin, Baihui; Huang, Huichuan; He, Xiahong; et al.
Summary: The Honghe Hani rice terraces system (HHRTS) is a traditional rice cultivation system where Hani people cultivate remarkably diverse rice varieties. Recent introductions of modern rice varieties to the HHRTS have significantly increased the severity of rice diseases within the terraces. Here, we determine the impacts of these recent introductions on the composition of the rice‐associated microbial communities. We confirm that the HHRTS contains a range of both traditional HHRTS landraces and introduced modern rice varieties and find differences between the microbial communities of these two groups. However, this introduction of modern rice varieties has not strongly impacted the overall diversity of the HHRTS rice microbial community. Furthermore, we find that the rice varieties (i.e. groups of closely related genotypes) have significantly structured the rice microbial community composition (accounting for 15%–22% of the variance) and that the core microbial community of HHRTS rice plants represents less than 3.3% of all the microbial taxa identified. Collectively, our study suggests a highly diverse HHRTS rice holobiont (host with its associated microbes) where the diversity of rice hosts mirrors the diversity of their microbial communities. Further studies will be needed to better determine how such changes might impact the sustainability of the HHRTS.